The Influence of Service Quality, Brand Image, and Customer Satisfaction on Purchase Intention at Global Art Tanjungpinang - Apriani, Ai; Sulistyowati, Tussi; Wasiman, Wasiman (SEIKO : Journal of Management & Business, 2024)
This research delves deeper into exploring and understanding the impact of service quality, brand image, and customer satisfaction on purchasing interest at Global Art Tanjungpinang. In a broader context, the study sheds light on the rapid development of education in Indonesia, accompanied by the emergence of non-formal educational institutions as indicators of sector progress. The research employs a quantitative descriptive method involving 150 carefully selected respondents, guests or visitors of Global Art Tanjungpinang, through purposive sampling. The intriguing findings of the research demonstrate brand image and customer satisfaction have a significant positive impact on purchasing interest, while service quality exerts a negative influence. The implications go beyond providing an in-depth understanding of the dynamics at Global Art Tanjungpinang, serving as a strategic foundation for the development and enhancement of services in non-formal education institutions. This becomes crucial in navigating intense competition and anticipating the needs of an increasingly complex market. Thus, the research offers a holistic perspective that can contribute valuable insights for stakeholders in the education sector.